Intravitreal Dexamethasone in Patients with Wet Age-Related Macular Degeneration Resistant to Anti-VEGF: A Prospective Pilot Study. (29th July 2018) - Giancipoli, Ermete; Pinna, Antonio; Boscia, Francesco; Zasa, Gianluigi; Sotgiu, Giovanni; Dore, Simone; D'Amico Ricci, Giuseppe
Abstract : Purpose . To evaluate the efficacy and safety of a single intravitreal dexamethasone implant (DXI) combined with intravitreal antivascular endothelial growth factor (anti-VEGF) therapy, in patients with neovascular age-related macular degeneration (wet-AMD) resistant to conventional treatment. Methods . In this randomized, controlled pilot study, 16 eyes of 15 patients, unresponsive to anti-VEGF therapy, were enrolled and randomly assigned to two groups: DXI + anti-VEGF (treatment group: 11 eyes) and monthly anti-VEGF alone (control group: 5 eyes). Patients were treated at baseline and followed for 6 months. Best corrected visual acuity (BCVA), optical coherence tomography (OCT) parameters, and fluorescein angiography (FA) were evaluated. Results . Eight eyes (72.7%) in the treatment group and 2 eyes in the control group (40%) showed complete retinal fluid resorption (p = 0.049 ). BCVA showed no significant change from baseline in both the treatment group and the control group (p = 0.40 andp = 0.29, respectively). Both median central foveal thickness (CFT) and median macular volume showed a greater reduction from baseline in the treatment group. Conclusion . In patients showing an incomplete response to anti-VEGF therapy, DXI combined with intravitreal anti-VEGF seems to improve retinal fluid resorption without functional advantage. This trial is registered withACTRN12618001102268 .